2019
DOI: 10.7150/thno.32720
|View full text |Cite
|
Sign up to set email alerts
|

Alarmin augments the antitumor immunity of lentiviral vaccine in ectopic, orthotopic and autochthonous hepatocellular carcinoma mice

Abstract: It is a daunting therapeutic challenge to completely eradicate hepatocellular carcinoma (HCC) from patients. Alpha-fetoprotein (AFP) -based vaccines appear promising, however the efficacy needs to be improved. Methods : Here, we explore if fusing high-mobility group nucleosome binding protein 1 (HMGN1), a potent immunoadjuvant, to AFP (lenti-HA) can augment the antitumor immunity of AFP-expressing lentiviral vector (lenti-AFP), a vehicle extensively employed for genetic immunization wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Therefore, the infiltration of activated CD4 memory T cells, CD8 T cells, and follicular helper T cells in the TME may be detrimental to the prognosis of HCC patients. Our inference is in line with the conclusion of Liu et al that intratumoural immunostimulated dendritic cells were critical for effective tumor rehabilitation, and improved immunotherapy with activated dendritic cells obtained a considerably stronger immune response against HCC cells [24]. Moreover, Zhang et al opined that high densities of tumor-infiltrating memory B cells signified an improved clinical outcome, which was associated with exceptional survival, and the high density of B cells correlated with a smaller tumor dimension and welldifferentiated tumor that was beneficial for therapeutic strategies to target B cells in HCC [25].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the infiltration of activated CD4 memory T cells, CD8 T cells, and follicular helper T cells in the TME may be detrimental to the prognosis of HCC patients. Our inference is in line with the conclusion of Liu et al that intratumoural immunostimulated dendritic cells were critical for effective tumor rehabilitation, and improved immunotherapy with activated dendritic cells obtained a considerably stronger immune response against HCC cells [24]. Moreover, Zhang et al opined that high densities of tumor-infiltrating memory B cells signified an improved clinical outcome, which was associated with exceptional survival, and the high density of B cells correlated with a smaller tumor dimension and welldifferentiated tumor that was beneficial for therapeutic strategies to target B cells in HCC [25].…”
Section: Discussionsupporting
confidence: 92%
“…This vehicle was extensively employed for genetic immunization with high transduction efficacy and a good safety profile. The antitumor immunity of Lenti-HA was assessed in ectopic, orthotopic, and autochthonous HCC models, demonstrating that HMGN1 increased the antitumor immunity of AFP-expressing lentiviral vaccines in HCC mice and human cells, and thus providing a new therapeutic strategy for HCC [139]. Moreover, several findings demonstrated that CAR T-cell immunotherapy targeting intracellular/secreted tumor antigens can elicit a potent antitumor response.…”
Section: Preclinical Studies In Hcc Immunotherapymentioning
confidence: 99%
“…Due to the absence of specific symptoms in eHCC and the lack of early diagnostic markers, most patients with HCC are often diagnosed in an advanced stage with poor prognosis (59,60), identifying that the characteristics of HCC initiation and development in the genomics and immune environment will contribute to enhancing our understanding of novel diagnostic markers for eHCC and TME pattern and guiding more effective immunotherapy strategies. The role of the tumor field effect of genomic instability and oncogene overexpression in HCC has gained much interest in recent years (61)(62)(63), and currently an altered TME is considered a promoter of cancer (64,65). Although under physiologic conditions immune disorder is an adaptive response to genetic alteration (66,67), when the immune disorder stimuli persist, the non-resolved immunodeficiency contributes to carcinogenesis (15,68).…”
Section: Discussionmentioning
confidence: 99%